2010
DOI: 10.3391/ai.2010.5.2.16
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of blue crab Callinectes sapidus Rathbun, 1896 in the Lagoon of Patok, Albania (south-east Adriatic Sea)

Abstract: This technical paper presents results from pilot field trials conducted on the novel use of a biodegradable jute material to eradicate the highly invasive aquatic macrophyte Lagarosiphon major Ridley from Lough Corrib, Ireland. The results demonstrate the ability of the jute material to comprehensively kill L. major and to restore native macrophyte communities to areas of the lake that were previously overgrown with this priority invasive species. To date, eight indigenous plant species (four charophytes and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…The first record in Hellenic waters dates back to 1947-1948(Serbetis, 1959, but Nehring (2011) suggested that the species was present as early as 1935 in the Gulf of Thessaloniki. Recent records in the Adriatic-Ionian Sea refer to Croatia (Onofri et al, 2008;Dulčić et al, 2011), Italy (Florio et al, 2008), Albania (Beqiraj and Kashta, 2010) and Greece (Eleftheriou et al, 2011). The last record was based on a female specimen collected close to the mouth of the River Pamisos in SW Greece and therefore, documentation on the presence of the species is lacking for a large part of the Eastern Ionian Sea, ranging from northern Albania to southern Greece.…”
Section: Documentation On the Establishment Ofmentioning
confidence: 99%
“…The first record in Hellenic waters dates back to 1947-1948(Serbetis, 1959, but Nehring (2011) suggested that the species was present as early as 1935 in the Gulf of Thessaloniki. Recent records in the Adriatic-Ionian Sea refer to Croatia (Onofri et al, 2008;Dulčić et al, 2011), Italy (Florio et al, 2008), Albania (Beqiraj and Kashta, 2010) and Greece (Eleftheriou et al, 2011). The last record was based on a female specimen collected close to the mouth of the River Pamisos in SW Greece and therefore, documentation on the presence of the species is lacking for a large part of the Eastern Ionian Sea, ranging from northern Albania to southern Greece.…”
Section: Documentation On the Establishment Ofmentioning
confidence: 99%
“…The crab under study can be considered as large, based on the HARDING (2003) classification which uses carapace width to classify blue crabs as small (CW<80 mm), medium (CW 80-120 mm) and large (CW>120 mm). The Greek specimen was smaller in comparison with others collected in France (CL=90 mm, VINCENT, 1986), in Albania (female CL=67-78,6 mm) (BEQIRAJ & KASHTA, 2010) or similar to that individual found in Spain (CL=45 mm, CABAL et al, 2006). The present decapod was considered to be mature, as the carapace width for mature females is between 120-170 mm (CADMAN & WEINSTEIN, 1985).…”
Section: F Callinectes Sapidus Rathbun In the Greek Ionian Seamentioning
confidence: 99%
“…Several records have been published in recent years, with regard to the species' distribution in the Adriatic (FLORIO et al, 2008) and other parts of the Mediterranean Sea, such as Spain (CABAL et al, 2006), and Albania (BEQIRAJ & KASHTA, 2010).…”
Section: F Callinectes Sapidus Rathbun In the Greek Ionian Seamentioning
confidence: 99%
“…This presence of adult males of C. sapidus in Boka Kotorska Bay suggests that this species might have established a population in the neighbouring area of Albania (Beqiraj & Kashta, 2010) and Croatia (Dulčić et al, 2011), so further research should be undertaken.…”
Section: First Record Of Callinectes Sapidusmentioning
confidence: 99%
“…Recent records in the eastern part of the Adriatic Sea refer to Croatia (Dulčić et al, 2011) and Albania (Beqiraj & Kashta, 2010).…”
Section: First Record Of Callinectes Sapidusmentioning
confidence: 99%